Music education in early childhood in Türkiye: How do school types affect the implementation of musical activities? - Songül Pektaş; Davut Elmacı (Anadolu Üniversitesi Eğitim Fakültesi dergisi, 2023)
This research aims to determine how the implementation of music in early childhood differs by the types of preschool institutions. The sample of the study, which was conducted with the qualitative research approaches, consists of 22 participants, 18 preschool teachers, and 4 school administrators working in four different types of public preschools. Research data were collected through semi-structured interviews. The school types in the study are 1 independent kindergarten, 1 primary school with preschool classes, 1 girls’ vocational high school with practice preschool classes, and 1 special education kindergarten. According to the research findings, music is used in all types of preschool institutions, and similar musical activities are carried out. However, while richer musical activities are carried out in independent kindergartens, the use of music in special education kindergartens is more limited. Independent kindergartens seem more advantageous than other school types in terms of implementing musical activities. Individual efforts of preschool teachers and their interest in music are more important in implementing musical activities. Although the participants highlight the importance of music in special education, the low skills of preschool teachers regarding the use of music in early childhood special education and the special needs of children make it difficult to use music in special education kindergartens.